Cardiovascular Gene Therapy: Past, Present, and Future - Ylä-Herttuala, Seppo (Mol Ther, 2017)
Cardiovascular diseases remain a large global health problem. Although several conventional small-molecule treatments are available for common cardiovascular problems, gene therapy is a potential treatment option for acquired and inherited cardiovascular diseases that remain with unmet clinical needs. Among potential targets for gene therapy are severe cardiac and peripheral ischemia, heart failure, vein graft failure, and some forms of dyslipidemias. The first approved gene therapy in the Western world was indicated for lipoprotein lipase deficiency, which causes high plasma triglyceride levels. With improved gene delivery methods and more efficient vectors, together with interventional transgene strategies aligned for a better understanding of the pathophysiology of these diseases, new approaches are currently tested for safety and efficacy in clinical trials. In this article, we integrate a historical perspective with recent advances that will likely affect clinical development in this research area.